Prospective comparison of 2D-shearwave elastography in both liver lobes in healthy subjects and in patients with chronic liver disease - Petzold, Golo; Grieme, Bastian; Bremer, Sebastian C B; Knoop, Richard F; Goetze, Robert G; Ellenrieder, Volker; Kunsch, Steffen; Neesse, Albrecht (Scandinavian journal of gastroenterology, 2019)
2D-shearwave elastography is an established method for liver stiffness measurement (LSM). However, the success rate of LSM using the recommended standard technique in the right lobe is limited by several factors. We aimed to compare LSM in the right and left liver lobe in order to evaluate whether LSM in the left lobe could be an alternative if measurements in the right lobe are not feasible. A total of 116 subjects, 58 healthy volunteers and 58 patients with chronic liver disease (CLD), were prospectively included. LSM were performed in the right lobe and in the left lobe, both in neutral and in inspiration position. LSM in the left lobe (8.39(±4.83)kPa) was significantly ( < .001) higher than LSM in the right lobe (6.27(±2.45)kPa). LSM in inspiration position (8.60(±4.33) kPa) was significantly ( = .009) higher than LSM in neutral position (7.70(±3.01)kPa). LSM in the left lobe overestimated the grade of fibrosis in 50.0% of the patients with CLD. However, correlation between LSM values right and left was strong ( = 0.856) and additional use of LSM in the left lobe increased the success rate from 106/116 (91.4%) to 112/116 (96.6%; = .098). High skin-to-liver-capsule-distance and presence of ascites were independent risk factors for non-successful LSM. Despite significantly higher values, LSM in the left lobe may be an alternative if LSM in the right lobe is not feasible, and cirrhosis can be ruled out with high probability if LSM is within the normal range.